"Evaluación de la capacidad clarificante de la Moringa oleifera (Moringa como coagulante en el producto fermentado de la Saccharum officinarum caña de azúcar" - Pérez Saldaña, Braulio Douglas (2017)
This research project was carried out with the objective of evaluating the clarifying power of Moringa oleifera (moringa) seeds in the process of clarifying the fermented juice of Saccharum officinarum (sugar cane) and verifying whether the seeds mentioned above have the same power clarifying that they have in the water, because it is already proven that its clarifying power is strong, in waters of rivers or lakes. For this purpose, three techniques for the application of moringa seeds (dissolved in distilled water, dissolved in water with sodium chloride and applied directly) were analyzed and applied to the solution in three different concentrations (5%, 10% and 15%) at fermented juice; The research was structured by an experimental design of complete random blocks with AxB factorial arrangement, from nine treatments and two repetitions with a total of 18 which allowed to determine the best treatments. The factors studied were: factor A (application techniques) and factor B (concentration of moringa). Data analysis was carried out using statistical software STATGRAPHICS CENTURION XVI, in order to define parameters and to verify significance, variables such as pH, acidity, total solids, density, alcoholic degrees and turbidity were studied, the most important one. Secondary analyzes such as higher alcohols, furfural, methanol, propanol, etc., were also performed by gas chromatography. The research concludes by stating that moringa seeds do have a significant clarification power in fermented juice. The results indicate that the treatment where the seeds of the moringa dissolve in distilled water with a concentration of 15% obtained the best clarification results when analyzing their turbidity, starting from 19.69 NTU to 4.42 NTU. Keywords: Techniques, seeds, concentration, turbidity, distilled.